Upaya Pecegahan Pornografi di SMP IT Bina Castrena Insani - Fuadah, Isma Samrotul; Sari, Resti Okta (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The development of technology in the digital era as it is today is growing faster from day to day, month to month to year in the future The presence of communication media and the rapid development of information communication technology facilitate the spread of pornographic material. A survey states that every year there are 72 million visitors to pornographic websites. In every second 28,000 internet users see pornographic content. Two-thirds of the pornography connoisseurs on the internet are men and the rest are women.